Al-zarnuji’s thought of Education and its Implementation at pesantren - Maslani Maslani; Ratu Suntiah; Yasniwarti Yasniwarti; Dadan Nurulhaq (Jurnal Pendidikan Islam, 2017)
The study aims to find out al-Zarnuji’s basic concept of knowledge, learning material, ethic, strategy, process and his contribution as well as to explain conceptual model on the basis of his thought at the institutions. In Pesantren Kebon Jambu al-Islami, Buntet and Bendakerep Cirebon, the Kitab Ta’līm al-Muta’allim is used as main reference of learning ethic. The study used qualitative research method. Source and kind of data were determined by the researcher as information center with purposive trait as long as it is supposedly representative.  The result indicates that the implementation of the book Ta’līm al-Muta’allim at those pesantrens was less satisfactory due to textual understanding. In order to effectively implement the book Ta’līm al-Muta’allim at those institutions, the contextual description is required.